Microstructure, mechanical and tribological properties of cold sprayed Ti6Al4V–CoCr composite coatings - Tan, Adrian Wei-Yee (2022)
Metal-matrix composite (MMC) coatings are advanced materials, composed of two or more phases that can be tailored based on the industrial needs such as lightweight and wear-resistance. Cold spray (CS) technology is highly suitable to develop these MMC coatings as it is a low temperature deposition method, which does not involve particle melting, hence retaining the original properties of the materials. Ti–6Al–4V (Ti64) is a common alloy used in aerospace applications owing to its lightweight and high yield strength. Recently, cold sprayed Ti64 coatings have shown promise to repair damaged or enhance surfaces of Ti components. However, there are still several issues with cold sprayed Ti64 coatings, such as relatively high porosity level and low wear-resistance. To solve these, a novel approach is to incorporate CoCr (ASTM F75) as reinforcing metal alloy particles into the Ti64 matrix to form a Ti64–CoCr composite coating. Pure Ti64 and pure CoCr coatings were also deposited as a comparison. The Ti64–CoCr composite coating achieved low porosity level (0.9%), high hardness (434 HV) and high wear resistance (1.7 × 10−4 mm3/Nm) compared to the Ti64 coatings. These properties were obtained while maintaining the original phases of the feedstock Ti64 and CoCr powders and achieving adhesion strength above 60 MPa. A 20 nm thick Ti–Co interdiffusion layer was also observed at the interface of CoCr and Ti64 particles under TEM. These results showed that Ti64–CoCr composite coating is a promising lightweight and wear resistant metallic coating for aerospace application.